Changing economic imaginaries: Making sense of consumption during the COVID-19 crisis - Lillqvist, Ella; Timonen, Päivi (Routledge, 2023)
This chapter analyses economic imaginaries, defined here as widely shared ways of understanding the future, the present and the enduring principles of the economic world. Specifically, our focus is on imaginaries that relate to consumption. Economic imaginaries can undergo change particularly during crises; this chapter therefore examines, in the context of Finland, whether and how economic imaginaries related to consumption transformed during the COVID-19 pandemic. The study makes use of large-scale aggregated news and social media data covering the years 2015–2021. We analyse this material using corpus-assisted discourse studies, an approach that combines quantitative and qualitative textual analysis. The keyword analysis method enables a comparison between the time period immediately before the COVID-19 crisis and the period of the pandemic. The chapter contributes to economic sociology by extending the theoretical discussion on the fictional aspects of the economy, as well as by widening the spectrum of methodological approaches used in the field.
Keywords: corpus-assisted discourse studies; crisis; economic sociology; imaginary; consumption; crises; fi=Viestintätieteet|en=Communication Studies|